Comparison study of the agricultural subsidy policy applied by Ecuador and Hungary in the last 10 years - Lourdes, Ordonez Maria; Kovács, Krisztián (Applied Studies in Agribusiness and Commerce, 2022)
Agricultural subsidies have long been a consistent concern of government policies; they influence the use of resources for pursuing different goals in this sector. In this research, we are making a comparison study of the agricultural subsidy policies of Ecuador and Hungary in the last ten years by a comparative analysis applied for empirical generalization to explain and get a better understanding of the subsidies used in the two countries. The results show an enormous advantage for Hungary compared to Ecuador regarding the agricultural subsidies. Since they are part of the Common Agricultural Policy of the European Union, Hungary's subsidies are institutionalized and planned in the long term within a series of programs financed by the EU and national funds. While in Ecuador, agricultural policies exist as a general framework, and the governing body manages the subsidies through programs and projects that do not remain over time and depend on the current political situation in the country. In the same way, the data collected reflects that although the share of the agricultural sector in Ecuador's GDP is higher than in Hungary, the subsidy amounts for this sector are 36% lower than in Hungary. JEL CODE: Q13